Comparative Efficacy and Safety of Tacrolimus Formulations - Wen, Ching Catherine (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Tacrolimus (FK 506), a lipophilic 23-member macrolide lactone, is a potent calcineurin inhibitor immunosuppressive drug and primarily acts as acute antirejection maintenances after organ transplantation. Tacrolimus has narrow therapeutic index, large inter and intra patient variability in pharma-kinetics profile and poor oral availability due its poor solubility, which indicate hardships in determination of its optimum dose to patients. Interactions with P-glycoprotein also contributes to inconsistent therapeutic levels. There have been a lot of efforts made in different formulation of tacrolimus in order to balance between therapeutic failure and toxicity. However, generally the non-adherence to tacrolimus immunosuppressive therapy has always been associated with adverse effects. This research investigates and compares the immediate-release (IR-Tac) and extended-release (ER-Tac) formulations, focusing on their impact on patient adherence, safety, and treatment efficacy. The results indicate that ER-Tac’s once-daily regimen improves adherence without compromising safety or efficacy, offering a promising alternative to the traditional twice-daily IR-Tac formulation.